Analysis of Adherence Factors to Tuberculosis Therapy at the PB Selayang II Health Center, Medan City - Hilda Sherman; Zulfa Ismaniar Fauzi; Zulfikri Zulfikri; Rosnike Merly Panjaitan; Rizkyanti Tarigan (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Pulmonary tuberculosis disease in Indonesia is increasing every year. The percentage of people receiving tuberculosis treatment as of 1 November 2022 is still far below the goal set (90%) or 52%. The 2020-2024 national health development strategy and the national medium term development plan 2020-2024 call for eliminating tuberculosis in Indonesia by 2030. Many factors can affect the success of tuberculosis treatment, including patient factors, drug ingestion monitor factors, and drug factors. This study aimed to determine the factors that influence therapy compliance in tuberculosis patients at the PB Selayang II Public health center, Medan City. This research method is quantitative analytical with a cross-sectional research design. The research was conducted at the PB Selayang II Public health center, Medan City, which was carried out from May to June 2023. The population in the study was all 109 tuberculosis patients. The sampling technique was purposive sampling, so the sample for this study was 56 patients. Data collection uses questionnaires with interviews. Data analysis using bivariate analysis using the chi-square test. The results of this study show that internal factors, namely taking anti-tuberculosis drugs, are related to compliance with a sig value of 0.002 and external factors, namely the role of officers and motivation, are related to compliance with tuberculosis therapy at PB Selayang II Public health center with a sig value of 0.000. The conclusion from the results obtained that significantly influences compliance with tuberculosis therapy is external factors where there are 2 categories related to compliance, namely motivation and the role of officers.Keywords: External factors, Internal factors, Public health center, Tuberculosis, Treatment compliance